2012
DOI: 10.1021/bm300149w
|View full text |Cite
|
Sign up to set email alerts
|

Supra-Molecular EcoBioNanocomposites Based on Polylactide and Cellulosic Nanowhiskers: Synthesis and Properties

Abstract: Successful filler dispersion and establishment of good interfacial contact with the surrounding matrix are essential for optimized reinforcement in polymeric nanocomposites. In particular, in renewable-based composites this can be challenging, where hydrophilic attractions between nanofillers facilitate aggregation. Here an innovative approach to prepare cellulosic nanowhisker (CNW) reinforced polylactide (PLA) is presented. The lactide ring-opening polymerization is initiated from CNW surface hydroxyl groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 48 publications
(74 reference statements)
0
85
1
Order By: Relevance
“…The other example of in situ esterification is the production of surface modified CNCs via one-pot reaction methodology, which combines organic acidcatalyzed Fischer esterification and concurrent cellulose acid hydrolysis of amorphous cellulose chains (Fig. 3a) Braun et al 2012;Sobkowicz et al 2009;Spinella et al 2016;Yu et al 2016). For example, acetylated and butylated CNCs were synthesized using acetic or butyric acid that both serves as the reaction solvent and reagent for the esterification at 105°C with the presence of hydrochloric acid as catalyst and hydrolyzing agent .…”
Section: In Situ Esterification During the Isolation Of Nanocellulosesmentioning
confidence: 99%
See 1 more Smart Citation
“…The other example of in situ esterification is the production of surface modified CNCs via one-pot reaction methodology, which combines organic acidcatalyzed Fischer esterification and concurrent cellulose acid hydrolysis of amorphous cellulose chains (Fig. 3a) Braun et al 2012;Sobkowicz et al 2009;Spinella et al 2016;Yu et al 2016). For example, acetylated and butylated CNCs were synthesized using acetic or butyric acid that both serves as the reaction solvent and reagent for the esterification at 105°C with the presence of hydrochloric acid as catalyst and hydrolyzing agent .…”
Section: In Situ Esterification During the Isolation Of Nanocellulosesmentioning
confidence: 99%
“…All three hydroxyl groups in the AGU including primary hydroxyl group at C6 and secondary hydroxyl groups at C2 and C3 (Fig. 1a) can participate in almost all the reactions as the alcoholic hydroxyl groups do, such as esterification, etherification, oxidation, silylation and polymer grafting Braun et al 2012;Coseri et al 2013;Dong and Roman 2007;Duan et al 2016;Filpponen and Argyropoulos 2010;Habibi et al 2010;Hasani et al 2008;Ma et al 2010;Mormann and Demeter 1999;Mormann and Wagner 1997;Pang et al 2016;Qiu and Hu 2013;Xu et al 2010;Yoo and Youngblood 2016). Among diverse chemical modifications, esterification represents one of the most promising technique, which was first adopted to synthesize cellulose derivatives (Klemm et al 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…Fractionation of the bers and the use of their constituents have been shown to be an important area for research. Within this eld, cellulose nano bril has considerable potential for use as reinforcement in polymers, due to its capacity to confer characteristics comparable to those achieved with synthetic materials [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere Braun et al demonstrated the ability of acetylated cellulose nanowhiskers to act as nucleants for PLA crystallization. The reduction of the crystallization half-time as well as increase of the crystallinity degree of PLA was reported (Braun et al 2012). In the work by Siqueira et al the crystallinity of PCL was increased by addition of sisal whiskers modified with n-octadecyl isocyanate while it was almost not influenced by the presence of microfibrillated cellulose bearing the same functional groups (Siqueira et al 2009).…”
Section: Dynamic Mechanical Analysis Of Pa410/mfc-ac Compositesmentioning
confidence: 93%